2016
DOI: 10.1186/s12968-016-0278-6
|View full text |Cite
|
Sign up to set email alerts
|

Aortic stiffening and its impact on left atrial volumes and function in patients after successful coarctation repair: a multiparametric cardiovascular magnetic resonance study

Abstract: BackgroundThe increased cardiovascular morbidity of adults with late repair of aortic coarctation (CoA) has been well documented. In contrast, successful CoA repair in early childhood has a generally good prognosis, though adverse vascular and ventricular characteristics may be abnormal, which could increase long-term risk. This study sought to perform a comprehensive analysis of aortic elasticity and left ventricular (LV) function in patients with aortic coarctation (CoA) using cardiovascular magnetic resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 41 publications
3
23
0
5
Order By: Relevance
“…There are multiple proposed contributors to the early age of stroke in patients with CoA. Long‐term vascular dysfunction and increased carotid intima‐medial thickness may increase the risk of ischemic stroke . In addition, CoA patients are more likely to be male and have hyperlipidemia .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are multiple proposed contributors to the early age of stroke in patients with CoA. Long‐term vascular dysfunction and increased carotid intima‐medial thickness may increase the risk of ischemic stroke . In addition, CoA patients are more likely to be male and have hyperlipidemia .…”
Section: Discussionmentioning
confidence: 99%
“…Long-term vascular dysfunction and increased carotid intima-medial thickness may increase the risk of ischemic stroke. 13,[34][35][36][37] In addition, CoA patients are more likely to be male and have hyperlipidemia. 38,39 There is a high prevalence (10%-12%) of intracranial aneurysms, which may predispose to hemorrhagic stroke.…”
Section: Coa and Age At Strokementioning
confidence: 99%
“…20,38 Most of the studies, evaluating pulse wave velocity in patients with coarctation of the aorta, have a heterogenous study population in terms of age including both adults and paediatric age groups. 9,27,[39][40][41] The studies which include only children and adolescents are scarce. 5,42 In general, these studies have shown increased pulse wave velocity (m/s) in the precoarctation aorta after successful repair of the coarctation compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of significant recoarctation, medical treatment of HT in this setting often follows the same algorithms applied for essential HT . An increase in left ventricular (LV) mass has been observed in several patients even in the absence of HT and is thought to be related to central aortic stiffness . This can in turn result in diastolic dysfunction and increase the risk of subendocardial ischemia and arrhythmias .…”
Section: Discussionmentioning
confidence: 99%
“…23 An increase in left ventricular (LV) mass has been observed in several patients even in the absence of HT and is thought to be related to central aortic stiffness. [24][25][26] This can in turn result in diastolic dysfunction and increase the risk of subendocardial ischemia and arrhythmias. 2 While CAD is a main contributor of increased mortality among repaired CoA patients, it is still uncertain whether there is an independent association between the two 27,28…”
Section: Discussionmentioning
confidence: 99%